EP424 Validation of the new FIGO 2018 staging system in clinically early cervical cancer. (1st November 2019) - van der Velden, J; Mom, CH; Spijkerboer, AM; Lonkhuijzen, LRCW van; Laan, JJ; Fons, G
Abstract : Introduction/Background: The new 2018 FIGO staging system imaging can be used for staging by analyzing the size of the primary tumor, the presence/absence of parametrial infiltration and the presence of metastatic lymph nodes. It was the aim of this study to compare the outcomes of the 'MRI' FIGO 2018 stage (r-stage) with the final pathological stage (p-stage), both in terms of accuracy and survival. Methodology: A retrospective analysis was performed on patients with early stage cervical cancer who were selected for surgical treatment on the basis of clinical parameters. Patients had a pre-operative MRI (3 × T2TSE, with axial HASTE pelvis and upper abdomen) and partial (lymph node dissection/debulking) or complete (radical hysterectomy and pelvic lymph node dissection) pathological staging. The accuracy of every individual r-stage was defined with the p-stage as 'golden standard'. Disease specific survival (DSS) of patients subdivided by r-stage was analyzed. Results: From 2001 till 2018, 438 surgically assessed/treated patients with FIGO 2009 stage IB1 and IB2 were analyzed. A pelvic lymph node dissection/debulking only or a radical hysterectomy with lymph node dissection was performed in 41 and 397 patients respectively. The accuracy of r-stage to predict p-stage is depicted in table 1. Cumulative Disease Specific Survival (DSS) according to r-stage is shown in Figure 1. Conclusion: R-stage IIB overestimates the risk on parametrial invasion (Positive predictive Value (PPV) from 6% to 28%) and therefore results in a better than expected 5 years disease specific survival of 89.7%. Although r-stage IIIC underestimates the risk on lymph node metastases (Negative Predictive Value (NPV) 81%), it correctly distinguishes the group with the poorest survival. The results from this retrospective study suggest that, at this stage, MRI imaging is not reliable enough to accurately predict p-stage IIB. Disclosure: Nothing to disclose.